Thinking about Thinking: Recent Research on the “Mind” in Ancient Israel - Grund-Wittenberg, Alexandra (Vetus Testamentum, 2025)
Two anthologies on the anthropology of the mind have appeared in the last years: J. Dietrich, Hebräisches Denken. Denkgeschichte und Denkweisen des Alten Testaments (BThSt 191; Göttingen Vandenhoeck & Ruprecht, 2022) and J. van Oorschot / L. Allolio-Näcke / A. Wagner, Archaeology of Mind in the Hebrew Bible / Archäologie alttestamentlichen Denkens (Berlin/Boston: De Gruyter, 2023). This contribution embeds them in the more recent developments in the study of thought, mentality, and concepts of personhood in ancient Israel.